2016
DOI: 10.5430/jnep.v6n12p34
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the implementation of sepsis guideline in a Canadian pediatric tertiary care centre

Abstract: Introduction: Adherence to Clinical Practice Guidelines for sepsis can improve care processes and outcomes; however, sepsis guideline adherence is plagued by many barriers. The purpose of this article is to report the perceived barriers for implementing a sepsis guideline at British Columbia's Children Hospital. Methods: This is a mixed method study. Data were collected from clinicians using a questionnaire that covered 3 major domains and included two open-ended questions. Quantitative data analysis focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Our findings demonstrated that the comprehensiveness, applicability, and perceived usefulness of the clinical guideline played a crucial role in its successful implementation. Although most of the participants in the study expressed that comprehensiveness and applicability were favorable factors for implementing the guideline, other studies have noted these factors as challenges [24,30]. For example, participants in the study of Hisham et al [31] believed that strict adherence to evidencebased recommendations and ignoring the role of clinical experiences in the guideline could pose a threat to its implementation and patient care.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our findings demonstrated that the comprehensiveness, applicability, and perceived usefulness of the clinical guideline played a crucial role in its successful implementation. Although most of the participants in the study expressed that comprehensiveness and applicability were favorable factors for implementing the guideline, other studies have noted these factors as challenges [24,30]. For example, participants in the study of Hisham et al [31] believed that strict adherence to evidencebased recommendations and ignoring the role of clinical experiences in the guideline could pose a threat to its implementation and patient care.…”
Section: Discussionmentioning
confidence: 96%
“…Attitudinal responses were also noted to have considerable impacts on guideline implementation. The results of Mosavianpour et al [30] showed that knowledge and positive attitudes were the factors that favourably affected the implementation of guidelines for managing sepsis in a pediatric hospital; on the other hand, motivational factors had the least role in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the nurse’s compliance with the Sepsis Six guidelines leads to decreased sepsis-related complication and mortality rates and improved clinical outcomes [ 26 ]. However, low adherence and compliance with applying the Sepsis Six guidelines are still unresolved issues impeding sepsis management due to several barriers [ 27 ]. Previous researchers have identified several barriers and facilitators to implementing the Sepsis Six guidelines [ 20 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the nurse's compliance with sepsis six guidelines leads to decrease in sepsis-related complication and mortality rates and improved clinical outcomes [22]. However, low adherence and compliance with applying sepsis six guidelines are still unresolved issues impeding sepsis management due to several barriers [23]. Previous researchers have identified several barriers and facilitators to the implementation of sepsis six guidelines [19,24].…”
Section: Introductionmentioning
confidence: 99%